KosConnect dengan Metode Google OAuth dan Payment Gateway Midtrans - Azzahra, Fathya Fathimah; Rosa Sekamayang, Balqis; Habibi, Roni (Jurnal PROCESSOR, 2025)
KosConnect is an innovative application that facilitates boarding house search, booking, and payment by integrating modern technologies to enhance user experience. As the demand for boarding houses increases and access to reliable information remains a challenge, KosConnect leverages Google OAuth for Single Sign-On (SSO) authentication, providing a more efficient and secure login process, while Midtrans serves as a payment gateway to enable fast and secure digital transactions. Developed using the Go programming language and MongoDB database, the application ensures optimal performance in data management while also offering personalization features to help users find accommodations that match their preferences. This project aims to streamline the login, registration, and payment processes by providing an integrated service that covers all stages from searching for boarding houses to completing transactions. The development results show that KosConnect effectively addresses the limitations of previous boarding house information systems, such as authentication that relies solely on email and password without SSO, bank transfers requiring manual proof uploads, and the lack of personalization features.